Candida albicans Colonizes and Disseminates to the Gastrointestinal Tract in the Presence of the Microbiota in a Severe Combined Immunodeficient Mouse Model - Pan, Chien-Hsiung; Lo, Hsiu-Jung; Yan, Jia-Ying; Hsiao, Yu-Ju; Hsueh, Jun-Wei; Lin, Di-Wei; Lin, Tsung-Han; Wu, Sze-Hsien; Chen, Yee-Chun (Frontiers in Microbiology, 2021)
Candida albicans is the leading cause of candidemia or other invasive candidiasis. Gastrointestinal colonization has been considered as the primary source of candidemia. However, few established mouse models that mimic this infection route are available. In the present study, we established a mouse model of disseminated candidiasis developed through the translocation of Candida from the gut. In this study, we developed a novel Candida albicans GI colonization and dissemination animal model by using severe combined immunodeficient Rag2-/-IL2γc-/- (Rag2γc) mice, which lack functional T, B, NK cells and IL2γc-dependent signaling. Rag2γc mice were highly susceptible to C. albicans gastrointestinal infection even in the presence of the gut microbiota. Within 4 weeks post infection, Rag2γc mice showed dose-dependent weight loss and disseminated candidiasis in more than 58% (7/12) of moribund mice. Histological analysis demonstrated abundant hyphae penetrating the mucosa, with significant neutrophilic infiltration in mice infected with wild-type C. albicans but not a filamentation-defective mutant. In moribund Rag2γc mice, the necrotic lesions and disrupted epithelial cells were associated with C. albicans hyphae. Notably, removal of the gut microbiota by antibiotics exacerbated the severity of fungal infection in Rag2γc mice, as demonstrated by elevated fungal burdens and accelerated weight loss and death. Furthermore, higher fungal burden and IL-1β expression were prominently noted in the stomach of Rag2γc mice. In fact, a significant increase in circulating proinflammatory cytokines, including IL-6, TNF-α and IL-10, indicative of a septic response, was evident in infected Rag2γc mice. Additionally, Rag2γc mice exhibited significantly lower levels of IL-22 but not IFN-γ or IL-17A than wild-type B6 mice, suggesting that IL-22 plays a role in C. albicans gastrointestinal infection. Collectively, our analysis of the Rag2γc mouse model revealed features of C. albicans gastrointestinal colonization and dissemination without the interference from antibiotics or chemotherapeutic agents, thus offering a new investigative tool for delineating the pathogenesis of C. albicans and its cross-talk with the gut microbiota.